Literature Review : Hubungan antara Kejadian Hiperurisemia pada Pasien Congestive Heart Failure - Nadiyah Nurfadhilah; Akina Maulidhany Tahir; Endy Adnan; Nurhikmawati Nurhikmawati (KOLONI, 2026)
Congestive heart failure (CHF) is a progressive clinical syndrome associated with high morbidity and mortality. Hyperuricemia has been suggested to contribute to the development and progression of CHF through several pathophysiological mechanisms, including oxidative stress, endothelial dysfunction, inflammation, and ventricular remodeling. This literature review aimed to evaluate the association between hyperuricemia and the incidence, severity, complications, and prognosis of CHF based on current scientific evidence. A narrative literature review was conducted using secondary data obtained from national and international scientific journals, textbooks, and other relevant scientific sources published between 2015 and 2026. The reviewed evidence consistently demonstrated that hyperuricemia is associated with poorer clinical outcomes in patients with heart failure. Elevated serum uric acid (UA) levels were correlated with higher New York Heart Association (NYHA) functional class, impaired hemodynamic status, increased risk of CHF occurrence, hospital readmission, and mortality across various heart failure phenotypes. Several studies also identified serum UA as an independent predictor of disease severity and prognosis in patients with heart failure. In conclusion, hyperuricemia is significantly associated with the severity and clinical outcomes of CHF and may serve as an important prognostic biomarker. However, current evidence regarding the effectiveness of uric acid-lowering therapy in improving heart failure prognosis remains inconsistent; therefore, serum UA cannot yet be recommended as a definitive therapeutic target.